Comparison of isokinetic muscular peak torque and power, bone speed of sound and body composition among Malaysian adolescent male sepak takraw players, volleyball players and sedentary individuals - Asri, Siti Nur Farhana; Foong, Kiew Ooi; Chee, Keong Chen; Mat Jawis, Mohd Nidzam; Md Hidzir, Haziaty; Samsudin, Norsuriani; Abidin, Muhammad Amrun Haziq (Faculty of Sports Science and Recreation, 2024)
This study investigated the differences of isokinetic muscular peak torque (PT) and average power (AVG.P), bone speed of sound and body composition among Malaysian adolescent male sepak takraw players, volleyball players and sedentary individuals. Thirty participants with mean age of 14.4 (1.4) years old participated in this study. The groups involved were sedentary control, sepak takraw and volleyball groups. Participant’s fat free mass and percent body fat were measured by body composition analyzer. Bone speed of sound of arms and legs were measured by bone sonometer. Knee and shoulder muscular PT (indicator of muscular strength) and AVG.P were measured by isokinetic dynamometer. There were statistically significant higher values of body height and fat free mass in volleyball players compared to sedentary controls. However, there were no significant differences in bone speed of sound between sedentary control, sepak takraw and volleyball groups. In general, volleyball and sepak takraw groups showed significantly higher values in most of the muscular PT and AVG.P measurements compared to the sedentary control group. Volleyball group showed statistically significant higher values compared to sepak takraw group in knee extension PT at 300⁰ .s¯¹, shoulder extension PT at 180⁰ .s¯¹and 300⁰ .s¯¹, and AVG.P at 300⁰ .s¯¹, as well as shoulder flexion PT at 60o .s¯¹, 180⁰ .s¯¹and 300o .s¯¹, AVG.P at 180⁰ .s¯¹and 300⁰ .s-1 . In conclusion, isokinetic knee extension, shoulder extension and flexion muscular strength and power are essential muscular performance variables in volleyball. Meanwhile, engagement in volleyball and sepak takraw could enhance muscular strength and power compared to sedentary lifestyle.